Organizational Resilience and Corporate Performance of Deposit Money Bank in Port Harcourt, Nigeria - Oparanma, A.O.; Ulunma, Elezie Patricia (International Journal of Business and Management Future, 2019)
This study examined the relationship between organizational resilience and corporate performance of deposit money banks in Port Harcourt. The general purpose was to examine the effect of organizational resilience on corporate performance of deposit money banks while the specific objectives are to examine the effect of organizational learning and adaptive capabilities on corporate performance. Twenty-one deposit money banks operating in Port Harcourt. Sixty three sample representatives were selected from the deposit money. Organizational resilience measures are organizational learning and adaptive capabilities while corporate performance measures are profitability, market share and employee satisfaction. Primary data were sourced through questionnaires and administered to managers at the regional office of the deposit money banks. Descriptive statistics and Spearman rank correlation coefficient with the aid of Statistical Packages for Social Science were used as data analyses techniques. Findings reveal a correlation coefficient of 81.4 percent and probability of 0.0000 between organizational learning and corporate performance. 89.4 percent and probability of 0.0000 between adaptive capabilities and corporate performance.  The finding indicates that organizational resilience has positive and significant relationship with corporate performance of the deposit money banks. It therefore recommends that techniques and strategic measures should be devise to enhance organizational resilience among the deposit money banks in Port Harcourt.